Measurement of neutrino-induced neutral-current coherent π0 production in the NOvA near detector (2019)
The cross section of neutrino-induced neutral-current coherent π0 production on a carbon-dominated target is measured in the NOvA near detector. This measurement uses a narrow-band neutrino beam with an average neutrino energy of 2.7 GeV, which is of interest to ongoing and future long-baseline neutrino oscillation experiments. The measured, flux-averaged cross section is σ ¼ 13.8 0.9ðstatÞ 2.3ðsystÞ × 10−40 cm2=nucleus, consistent with model prediction. This result is the most precise measurement of neutral-current coherent π0 production in the few-GeV neutrino energy region.